Travail et syndicalisme: naissance et évolution d'une action sociale - Thwaites, James D. (Presses de l'Université Laval, 2002)
Keywords: Travail

Travail et syndicalisme: origines, évolution et défis d'une action sociale - Thwaites, James D. (Presses de l'Université Laval, 2007)
Keywords: Travail

Travail et syndicalisme: origines, évolution et défis d'une action sociale - Thwaites, James D. (Presses de l'Université Laval, 2014)
Keywords: Travail

Le travail et la classe ouvrière montréalaise au XIXe siècle - Petitclerc, Martin (Histoire de Montréal et de sa région, 2012)
Keywords: Chevaliers du Travail; Conseil des métiers et du travail de Montréal; Grande Association; Grèves; Pauvreté; Syndicats internationaux; Travail

Ethnic Partition of the Work Force in 1840s Montréal - Olson, Sherry (Labour / Le travail, 2004)
Keywords: Anglophones; Britanniques; Français; Irlandais; Protestants; Travail

Le travail des femmes célibataires de l'élite et la famille pendant la période préindustrielle à Montréal - Fortin, Jonathan (L'argent des familles. Pratiques et régulations sociales en Occident aux XIXe et XXe siècles, 2019)
Keywords: Famille; Femmes; Fourrure; Marchands; Travail

Le célibat féminin à Québec et Montréal au XVIIIe siècle: travail, famille et sociabilité - Fortin, Jonathan (Université de Sherbrooke, 2016)
Keywords: Famille; Femmes; Marchands; Travail

La grève générale des charpentiers-menuisiers de Montréal, 1833–1834 : réévaluation d’un acte fondateur autour du concept de légitimité - Tremblay, Robert (Labour / Le travail, 2018)
Keywords: Charpentiers; Grèves; Libéralisme; Maçons; Menuisiers

L'histoire des cols bleus regroupés de Montréal. Tome 1: De ses origines à 1963 - Lapierre, Jean (2008)
Keywords: Travail

Compassion, association, utopie. La mutualité ouvrière à Montréal au milieu du XIXe siècle - Petitclerc, Martin (Revue du MAUSS, 2008)
Keywords: Assurance; Travail

The Decline of Apprenticeship in North America: Evidence from Montreal - Hamilton, Gillian (Journal of Economic History, 2000)
Keywords: Apprentissage; Travail

Les jardiniers professionnels de Montréal au XVIIIe siècle - Fortin, Guillaume (Université du Québec à Montréal, 2019)
Keywords: Jardins; Travail

Note de recherche. Les journaliers dans le district de Montréal en 1831 - Dessureault, Christian (Revue d'histoire de l'Amérique française, 2021)
Keywords: Famille; Recensements; Travail

La petite histoire, des origines jusqu'à 1925. Des carrières sous le parc Laurier - Côté, Julie; Cudia, Caroline (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2019)
Keywords: Carrière; Parcs; Travail

L’émergence d’un mouvement. Les premières sociétés de secours mutuels canadienne-française à Montréal, (1851-1867) - Bischoff, Peter C. (Cap-aux-Diamants, 2018)
Keywords: Assurance; Travail; Union Saint-Joseph

Parent, Lanctôt et Helbronner. Trois figures de l’économie sociale au XIXe siècle - Petitclerc, Martin (Cap-aux-Diamants, 2018)
Keywords: Helbronner, Jules; Lanctôt, Médéric; Travail

Labour and the Montreal Working Class in the Nineteenth Century - Petitclerc, Martin (Montreal: The History of A North American City, 2018)
Keywords: Chevaliers du Travail; Conseil des métiers et du travail de Montréal; Grande Association; Grèves; Pauvreté; Syndicats internationaux; Travail

En rade: marins à Montréal (1851-1896) - Bélisle-Desmeules, David (Domaine histoire, 2019)
Keywords: Navigation; Port; Travail; Vieux-port

Population, identités sociales et vie quotidienne - Gauvreau, Danielle (Histoire de Montréal et de sa région, 2012)
Keywords: Famille; Femmes; Irlandais; Mortalité; Travail; Veuvage

Population, Social Identities, and Daily Life - Gauvreau, Danielle (Montreal: The History of A North American City, 2018)
Keywords: Famille; Femmes; Irlandais; Mortalité; Travail; Veuvage

Histoire des communautés noires au Québec et à Montréal (2e partie) - Tessier, Stéphane (Il était une fois... Montréal-Nord, 2020)
Keywords: Chemins de fer; Musique; Noirs; Travail

Le syndicalisme québécois: deux siècles d'histoire - Rouillard, Jacques (Boréal, 2004)
Keywords: Confédération des syndicats nationaux; Confédération des travailleurs catholiques du Canada (C.T.C.C.); Fédération des travailleurs et travailleuses du Québec (FTQ); Grèves; Travail

Deindustrializing Montreal: Entangled Histories of Race, Residence, and Class - High, Steven C (Études d'histoire du Québec / Studies on the History of Quebec, 2022)
"Point Saint-Charles, a historically white working-class neighbourhood with a strong Irish and French presence, and Little Burgundy, a multiracial neighbourhood that is home to the city's English-speaking Black community, face each other across Montreal's Lachine Canal, once an artery around which work and industry in Montreal were clustered and by which these two communities were formed and divided. Deindustrializing Montreal challenges the deepening divergence of class and race analysis by recognizing the intimate relationship between capitalism, class struggles, and racial inequality. Fundamentally, deindustrialization is a process of physical and social ruination as well as part of a wider political project that leaves working-class communities impoverished and demoralized. The structural violence of capitalism occurs gradually and out of sight, but it doesn't play out the same for everyone. Point Saint-Charles was left to rot until it was revalorized by gentrification, whereas Little Burgundy was torn apart by urban renewal and highway construction. This historical divergence had profound consequences in how urban change has been experienced, understood, and remembered. Drawing extensive interviews, a massive and varied archive of imagery, and original photography by David Lewis into a complex chorus, Steven High brings these communities to life, tracing their history from their earliest years to their decline and their current reality. He extends the analysis of deindustrialization, often focused on single-industry towns, to cities that have seemingly made the post-industrial transition. The urban neighbourhood has never been a settled concept, and its apparent innocence masks considerable contestation, divergence, and change over time. Deindustrializing Montreal thinks critically about locality, revealing how heritage becomes an agent of gentrification, investigating how places like Little Burgundy and the Point acquire race and class identities, and questioning what is preserved and for whom."--
Keywords: Gentrification; Irlandais; Lachine (canal); Noirs; Petite-Bourgogne; Pointe-Saint-Charles; Quartiers; Travail

"Ils ne sont plus le peuple qu’ils étaient hier": la culture ouvrière à Montréal-Est au moment de la Confédération - Petitclerc, Martin; Bellavance, Claude; St-Hilaire, Marc (Le fait urbain, 2020)
Keywords: Cartier, Georges-Étienne; Lanctôt, Médéric; Montréal-Est; Partis politiques; Quartiers; Rouges; Saint-Jacques; Saint-Louis; Sainte-Marie; Travail; Élections

Carrières et pierre grise (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2019)
Keywords: Carrière; De Lorimier (village); Géographie physique; Géologie; Histoire naturelle; Parcs; Plateau Mont-Royal; Quartiers; Travail; Villages; Églises

L'industrie de la chaussure à Montréal, 1840-1870: le passage de l'artisanat à la fabrique - Burgess, Joanne (Travail et syndicalisme: naissance et évolution d'une action sociale, 2002)
Keywords: Artisans; Chaussure

Women’s Workplaces: The Impact of Technological Change on Working-Class Women in the Home and in the Workplace in Nineteenth Century Montreal - Bradbury, Bettina (Rethinking Canada. The Promise of Women’s History, 2002)
Keywords: Femmes; Travail

''L’association qui crée une nouvelle famille''. L’expérience populaire de la mutualité lors de la transition à l’économie de marché - Petitclerc, Martin (Revue d'histoire de l'Amérique française, 2006)
Keywords: Assurance; Travail

Albert Saint-Martin, militant d'avant-garde. Hochelaga 1865 – Faubourg Saint-Jacques 1947 - Larivière, Claude (Les Éditions de la Rue Dorion, 2021)
Keywords: Groupes populaires; Idéologies; Socialistes; Travail

Left Out of the Official History. The Women of St Anne's Market - Poutanen, Mary Anne; Olson, Sherry (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Femmes; Marchés; Sainte-Anne (marché); Travail

Oubliées de l'histoire officielle. Les femmes du marché Sainte-Anne - Poutanen, Mary Anne; Olson, Sherry (Montréal capitale. L'exceptionnelle histoire du site archéologique du marché Sainte-Anne et du parlement de la province du Canada, 2021)
Keywords: Femmes; Marchés; Sainte-Anne (marché); Travail

L’émeute de Lachine en 1812: la coordination d’une contestation populaire - Dessureault, Christian (Revue d'histoire de l'Amérique française, 2008)
Keywords: Lachine; Émeutes

Les pionniers du mouvement ouvrier au Québec: quelques pistes de réflexion sur la première génération de militants des années 1830 - Tremblay, Robert (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 2012)
Keywords: Charpentiers; Chaussure; Confection; Imprimerie; Menuisiers

Baptizing Novices: Ritual Moments among French Canadian Voyageurs in the Montreal Fur Trade, 1780-1821 - Podruchny, Carolyn (Canadian Historical Review, 2002)
Keywords: Fourrure

Des emplois pour une élite cultivée: travailler pour l’Assemblée législative de la province du Canada, 1840-1850 - Roy, Alain (Bulletin d'histoire politique, 2017)
Keywords: Fonctionnaires; Parlement

Solemn Processions and Terrifying Violence: Spectacle, Authority, and Citizenship during the Lachine Canal Strike of 1843 - Horner, Dan (Urban History Review / Revue d'histoire urbaine, 2010)
Keywords: Grèves; Irlandais; Lachine (canal)

WARREN, GEORGE STEPHENS - Rouillard, Jacques (Dictionnaire biographique du Canada, 2005)

Artisans et ouvriers à l’époque des revendications démocratiques et nationalitaires du Parti patriote dans le Bas-Canada, 1832-1838: un rendez-vous manqué avec l’histoire ? - Tremblay, Robert (Bulletin d'histoire politique, 2017)
Keywords: Partis politiques; Tracey, Daniel; Élections

Main-d'oeuvre immigrante et développement dualiste: l'économie canadienne au milieu du XIXe siècle - Seccareccia, Mario; Saint-Germain, Maurice (Histoire sociale / Social History, 2001)
Keywords: Britanniques

Les Irlandais et le canal de Lachine. La grève de 1843 - Boily, Raymond (Leméac, 2011)
Keywords: Grèves; Irlandais; Lachine (canal)

Saving the Union's Jack: The Montreal Sailor's Institute and the Homeless Sailor, 1862-98 - Ingram, Darcy (Negotiating Identities in 19th- and 20th- Century Montreal, 2005)

À chacune son rang. Les ''filles données'' des Soeurs Grises 1855-1905 - Gervais, Diane (Revue d'histoire de l'Amérique française, 2014)
Keywords: Communautés religieuses; Domestiques; Femmes; Soeurs Grises

Taking to the Streets: Crowds, Politics, and the Urban Experience in Mid-Nineteenth-Century Montreal - Horner, Dan (Études d'histoire du Québec / Studies on the history of Quebec, 2020)
Keywords: Grèves; Incendies; Lachine (canal); Parlement; Rues; Rébellions; Réformistes; Émeutes

VERVILLE, ALPHONSE - Leroux, Éric (Dictionnaire biographique du Canada, 2005)

LESPÉRANCE, ZOTIQUE - Rouillard, Jacques (Dictionnaire biographique du Canada, 2005)

Butcher, Baker, Cabinetmaker? A View of Montreal's Scottish Immigrant Community from 1835 to 1865 - McNabb, Heather (A Kingdom of the Mind: How the Scots Helped Make Canada, 2006)
Keywords: Écossais

HELBRONNER, JULES - de Bonville, Jean (Dictionnaire biographique du Canada, 2005)

Une forme d'entraide populaire: histoire des sociétés québécoises de secours mutuels au 19e siècle - Petitclerc, Martin (Université du Québec à Montréal, 2004)
Keywords: Assurance; Banques; Pauvreté; Union Saint-Joseph

Tanneurs et tanneries dans le gouvernement de Montréal au XVIIIe siècle - Perrier, Jocelyne (Université de Montréal, 2002)
Keywords: Artisans; Tannerie

Les couturières de Montréal au XVIIIe siècle - Gousse, Suzanne (Septentrion, 2013)
Keywords: Confection; Femmes

Aspects démographiques de la vie des couturières de Montréal au XVIIIe siècle - Gousse, Suzanne (Cahiers d'histoire, 2010)
Keywords: Confection; Femmes

Le règne de la scientificité: histoire de l'étiologie des maladies infectieuses dans la presse médicale du Québec, 1840-1880 - Beaudry, Louka (Université de Montréal, 2013)
Keywords: Médecine

FABIEN, CLÉOPHAS - Tremblay, Robert (Dictionnaire biographique du Canada, 2005)

GUYON, LOUIS - Dionne, Jean-Claude (Dictionnaire biographique du Canada, 2020)

CURRY, NATHANIEL - Sutherland, David A. (Dictionnaire biographique du Canada, 2019)

LAPORTE, sir HORMISDAS - Poitras, Claire (Dictionnaire biographique du Canada, 2018)

DAWSON, ARTHUR OSBORNE - Miller, Carman (Dictionnaire biographique du Canada, 2023)